An Efficient Schema for Cloud Systems Based on SSD Cache Technology. (31st October 2013) - Liu, Jinjiang; Lan, Yihua; Liang, Jingjing; Cheng, Quanzhou; Hung, Chih-Cheng; Yin, Chao; Sun, Jiadong
Abstract : Traditional caching strategy is mainly based on the memory cache, taking read-write speed as its ultimate goal. However, with the emergence of SSD, the design ideas of traditional cache are no longer applicable. Considering the read-write characteristics and times limit of erasing, the characteristics of SSD are taken into account as far as possible at the same time of designing caching strategy. In this paper, the flexible and adaptive cache strategy based on SSD is proposed, called FAC, which gives full consideration to the characteristics of SSD itself, combines traditional caching strategy design ideas, and then maximizes the role SSD has played. The core mechanism is based on the dynamic adjustment capabilities of access patterns and the efficient selection algorithm of hot data. We have developed dynamical adjust section hot data algorithm, DASH in short, to adjust the read-write area capacity to suit the current usage scenario dynamically. The experimental results show that both read and write performance of caching strategy based on SSD have improved a lot, especially for read performance. Compared with traditional caching strategy, the technique can be used in engineering to reduce write times to SSD and prolong its service life without lowering read-write performance.